2005
DOI: 10.1007/s10740-005-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Swirling Flows in Vortex Tubes

Abstract: Complete Navier-Stokes equations are solved numerically for the case of an intense swirling flow in an axisymmetric channel with an orifice plate in the delivery cross section and a throttle in the form of a peripheral slit at the opposite end. Flow patterns and velocity and temperature fields are obtained. The presence of precession of axial vortex is observed, as well as the formation of large-scale vortex structures. The numerical calculation results are compared for the first time with the experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 3 publications
2
12
0
Order By: Relevance
“…For example, using a simple vortex tube model with CFX software and k-ε turbulence model, Kazantseva et al [26] attributed the energy separation inside the VT to the energy and gas dynamic interaction of vortices inside the VT. Behara et al [27] modeled the RHVT using STAR-CD software and concluded that the energy separation inside the VT exists due to the shear work and heat transfer between the hot and cold streams. Bovand et al [28] studied a 3D model of the VT and concluded that a large portion of the energy transfer inside the RHVT is due to the tangential viscous shear.…”
Section: Energy Separation Inside the Rhvtmentioning
confidence: 99%
“…For example, using a simple vortex tube model with CFX software and k-ε turbulence model, Kazantseva et al [26] attributed the energy separation inside the VT to the energy and gas dynamic interaction of vortices inside the VT. Behara et al [27] modeled the RHVT using STAR-CD software and concluded that the energy separation inside the VT exists due to the shear work and heat transfer between the hot and cold streams. Bovand et al [28] studied a 3D model of the VT and concluded that a large portion of the energy transfer inside the RHVT is due to the tangential viscous shear.…”
Section: Energy Separation Inside the Rhvtmentioning
confidence: 99%
“…Free and Forced vortex regimes were identified and it was concluded that 6-nozzles of convergent shape produce better results. Kazantseva et al observed (Kazantseva, Piralishvili, & Fuzeeva, 2005) (Farouk & Farouk, 2007) LES turbulence model to vortex tube and concluded that LES can successfully simulate the conditions in vortex flow field and can give results very much close to measured ones. Akhesmeh et al confirmed (Akheshmeh, Pourmahmoud, & Sedgi, 2008) the accuracy of standard k-ε model while working with 3-D sector model with standard k-ε turbulence scheme.…”
Section: Introductionmentioning
confidence: 90%
“…However, the proposal regarding the compression inside a vortex tube is not particularly convincing, primarily due to the internal pressure profile, as discussed in previous research [1,22]. On the other hand, a general agreement regarding the expansion process with the tube as being the dominating factor for the temperature drop has also been observed in literature [1,14,25,26,29]. It has, furthermore, been reported that the cooling performance of a vortex tube depends on the properties of the working gases.…”
Section: Introductionmentioning
confidence: 92%
“…Different understandings of the internal flow mechanisms and explanations for the energy separation within the vortex tube, which have been reviewed and analysed in recent publications [19][20][21][22], imply the lack of general consensus and the requirement of clarification of the complex separating phenomenon. The internal pressure gradient has been proposed as the dominating factor for the energy separation phenomenon within a vortex tube [14,[23][24][25][26]. Ranque proposed that compression and expansion effects are the main reasons for the temperature separation in the tube [7,27].…”
Section: Introductionmentioning
confidence: 99%